HUBUNGAN SANITASI LINGKUNGAN DENGAN KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS MOJOTENGAH - Ihsani Akmalia; Ari Setyawati; Nazilla Nugraheni (Jurnal Ilmiah Kesehatan, 2024)
Diarrheal disease is still a global problem with a high degree of morbidity and mortality in various countries and is one of the main causes of high morbidity and mortality in children under the age of 5 in the world. One of the causes is influenced by environmental factors such as clean water facilities, latrines and waste water disposal facilities (SPAL). This study aims to determine the relationship between environmental sanitation and the incidence of diarrhea in toddlers in the Working Area of the Mojotengah Health Center. This study used an analytic observational design with a cross-sectional approach, with a sample of 117 respondents and the sampling technique used was purposive sampling. The analysis technique uses the chi-square test. The results showed that there was a relationship between clean water recommendations (p value = 0.05), family latrine facilities (p value = 0.02), and waste water sewer facilities (p value = 0.00). with the incidence of diarrhea in toddlers in the Working Area of the Mojotengah Public Health Center